The Effect of Problem Based Learning Model on Mathematics Learning Outcomes of Class VIII Students at SMP Negeri 10 Bengkulu City - Aina Novita Irka (CV Media Inti Teknologi, 2024)
Learning outcomes was the accomplishments of educational purpose for students who take part in the teaching and process of learning, student outcomes of learning are fundamentally behavioral changes brought about by learning. According to the findings, it was discovered that the outcomes of learning in mathematics of Class VIII students of SMPN 10 Kota Bengkulu for the 2022/2023 academic year were still low. So that the effort that can be made to increase student outcomes of learning in mathematics is to apply problem based learning learning models. This research purpose to see whether the the outcomes of learning in mathematics of students who study using the problem-based learning model in class VIII SMP Negeri 10 Kota Bengkulu was more good than the outcomes of learning by students using learning in conventional models.This research type was a quasi-experimental design with a non-equivalent posttest only control group design. The selection for sample was conducted using technique by simple random sampling, so that class VIIID was selected as the class for experimental and class VIIC as the class for control. The instruments in research were in consist of quizzes and final tests outcomes of learning in the form of essays. According on the research data analysis results at the real level α = 0.05 using the t test obtained P-value = 0.018, that means that P-value < ???? so reject H0. This shows that the outcomes of learning by students in mathematics who study using the model of problem-based learning are more good than students who study using learning in models of conventional in class VIII SMPN 10 Kota Bengkulu.